Splenic Infarction Associated with Covid-19 in Pediatrics: Case Report - Mata, Elvia Torres; Flores Uzcanga, Maura Alicia; Anzures, Edgar Omar Narvaez (British Journal of Healthcare and Medical Research, 2023)
SARS-CoV-2 disease is a recently emerged infection that caused a global pandemic, declared by the World Health Organization in March 2020. It had an impact on pediatric health, highlighting the relationship between inflammation, hypercoagulability, and vascular thrombosis. We present the case of a 10-year-old female patient who experienced splenic infarction associated with Covid-19, successfully treated with open splenectomy and low molecular weight heparin anticoagulation. Coagulation abnormalities in Covid-19 patients have been described since the early cases observed in Wuhan, China, but there is limited information on their presence in pediatrics. The unusual case we present could represent a manifestation of these alterations.